Impact of acute-on-chronic liver failure and decompensated liver cirrhosis on psychosocial burden and quality of life of patients and their close relatives - Nagel, Michael (Health Qual Life Outcomes, 2020)
BACKGROUND: Patients with liver cirrhosis often suffer from complications such as ascites, gastrointestinal bleeding, and infections, resulting in impaired quality of life. Frequently, the close relatives of patients also suffer from a lower quality of life in chronic diseases. In recent years, acute-to-chronic liver failure has been defined as a separate entity with high mortality. Often several organs are affected which makes intensive care therapy necessary. Little is known about the influence of acute-on-chronic-liver failure (ACLF) on the quality of life of patients and the psychosocial burden on close relatives. AIM: The purpose of this prospective study is to investigate the influence of decompensated liver cirrhosis and the onset of ACLF of the patient’s’ quality of life and the psychosocial burden of close relatives. METHOD: In this non – randomized prospective cohort study a total of 63 patients with acute decompensation of liver cirrhosis and hospital admission were enrolled in the study. To assess the quality of life of patients, the disease specific CLDQ questionnaire was assessed. In addition. Quality of life and psychosocial burden of first degree relatives was measured using the generic SF-36 questionnaire as well as the Zarit Burden Score. RESULTS: 21 of the 63 patients suffered from ACLF. Patients with ACLF showed a lower quality of life in terms of worries compared to patients with only decompensated liver cirrhosis (3,57 ± 1,17 vs. 4,48 ± 1,27; p value: 0,008) and increased systemic symptoms (3,29 ± 1,19 vs. 4,48 ± 1,58; p value: 0,004). The univariate analysis confirmed the link between the existence of an ACLF and the concerns of patients. (p value: 0,001). The organ failure score was significantly associated with overall CLDQ scores, especially with worries and systemic symptoms of patients. Interestingly the psychosocial burden and quality of life of close relative correlates with patient’s quality of life and was influenced by the onset of an acute-on-chronic liver failure. CONCLUSION: Patients with decompensated liver cirrhosis suffer from impaired quality of life. In particular, patients with ACLF have a significantly reduced quality of life. The extent of the psychosocial burden on close relative correlates with poor quality of life in patients with decompensated liver disease and is influenced by the existence of ACLF.